Avaliação de similaridade genética por Random Amplifed Polimorphic DNA (RAPD-PCR) entre as cepas de Helicobacter pylori em adultos e em seus familiares - Maciel, Felipe Silva (2020)
Helicobacter pylori infects approximately 50% of the world's population, with variable prevalence, this related to the economic development of the country. Molecular studies of H. pylori reinforce the hypothesis, that the transmission of the bacteria occurs in the family group occurs mainly between mother and son, as well as between brothers. In first-degree relatives of patients with gastric cancer, occur more frequent changes in the gastric mucosa. Considering the infection since childhood is greater than the risk of developing gastric cancer in individuals with a family history of gastric cancer, the analysis of the molecular pattern of H. pylori strains in the family is an important tool to determine the follow-up of those individuals. Thus, this work had the objective of realizing a genomic analysis among the strains of H. pylori in patients with gastric cancer and their families. The study was conducted in the laboratory of Gastroenterology of the Federal University of Ceará. 41 individuals were evaluated positive for h. pylori, divided into 8 families with 1 case of gastric cancer (index case) in each, and 72 individuals without gastric pathologies. The genomic DNA of H. pylori was extracted from the biopsies of patients with cancer, and their families to identify the main virulence markers, as well as of individuals control. Then DNA fingerprints were obtained by RAPD-PCR, subsequently analyzed in the software GelJ 2.0., determining the similarity of the strains. The non-parametric Mann Whitney test was used for comparison of the similarities between the families and the population with no family relationship. We considered statistically different the value of p < 0.05. The average similarity of all the families was 18.24% versus 8.12% of the population with no family relationship (72 individuals), (p < 0.001). The average similarity of each family when compared to population with no family relationship was significantly higher, ranging from 10.00-44.44% versus 8.12% (p < 0.05). Thus the results of this study point to the need for close monitoring of the relatives of individuals with gastric cancer, especially the brothers, because of the high similarity of the strains in the family niche.